Understanding the Financial Dynamics of SMEs: The Impact of Literacy, Inclusion, and Education on Financial Behavior in Small Food Stall Businesses in Bekasi Regency - Elkarima, Naseha; Khaddafi, Muammar; Daniel; Efna, Desi; Eva, Kemistia; Rickiany, Liza; Dewi Anggraeni, Poppy; Andrian, Nopy; Abyadi, Syaidil (International Journal of Advanced Multidisciplinary, 2024)
This research explores the intricate financial dynamics of Small and Medium-sized Enterprises (SMEs) by investigating the influence of financial literacy, financial inclusion, and education on the financial behavior of small food stall businesses in Bekasi Regency. The study confirms that financial literacy significantly and positively affects the financial behavior of food stall entrepreneurs, emphasizing its role in effective financial management. Financial inclusion also plays a pivotal role, with a positive correlation between access to financial services and favorable financial behavior, though disparities in utilization exist. Moreover, education exhibits a significant positive influence on financial behavior, highlighting the benefits of higher education levels among entrepreneurs. In conclusion, this study underscores the importance of enhancing financial literacy and inclusion initiatives for SMEs to promote sound financial practices and informed decision-making. These insights are valuable for policymakers, financial institutions, and SME support organizations seeking to foster the growth and sustainability of small businesses in the region.